The effect of hollow section to the flexural strength of the beam - Muhamad Afiq , Azman (2013)
The idea of providing hollow section to the beam in order to reduce the weight of the structure was generally one of the solutions for lightweight beam structure. The concept introduced was the same as hollow slab panels which been widely used in bridge and highway construction. The reduction of the surface area of the beam will give an effect on the bending moment and shear resistance of the beam therefore, an experimental testing was necessary in order to identify the flexural strength, deflection profile and crack pattern of the hollow beam samples. Beam.dimension of (150x200x3000)mm were sampled into Beam 1, Beam 2, Beam 3 and Beam 4. Beam 1 was solid beam with no hollow while Beam 2, Beam 3 and Beam 4 were beam sample with hollow size of (45x45)mm, (70x70)mm and (95x95)mm respectively. For flexural strength, the beam samples were tested under 4-point flexural test and Linear Variable Displacement Transducer (LVDT) were used to measure the deflection of the samples. The crack pattern of beam samples were observed throughout the experiment and the cracking were then analyzed accordingly. The result shows that the flexural strength of the samples reduced to certain degree of percentage of 12.64%, 16.14% and 17.16% for Beam 2, Beam 3 and Beam 4 respectively. Result for deflection shows that Beam 2, Beam 3 and Beam 4 deflected more compared to Beam 1 with percentage increment of 6.27%, 3.19% respectively. As for deflection profile, Beam 1, Beam 2, Beam 3 and Beam 4 show the same profile. Cracking pattern result shows same behavior between all samples while first crack loading result for Beam 1, Beam 2, Beam 3 and Beam 4 was 3lkN, and 15.74% 28kN, 23kN, and 2lkN respectively.